Effects of temperature stress on the accumulation of ascorbic acid and folates in sweet corn (Zea mays L.) seedlings. (24th December 2019) - Xiang, Nan; Hu, Jianguang; Wen, Tianxiang; Brennan, Margaret Anne; Brennan, Charles Stephen; Guo, Xinbo
Abstract: BACKGROUND: Extreme temperatures are among the primary abiotic stresses that affect plant growth and development. Ascorbic acid (AsA) is an efficient antioxidant for scavenging relative oxygen species accumulated under stress. Folates play a significant role in DNA synthesis and protect plants against oxidative stress. Sweet corn ( Zea mays L.), a crop grown worldwide, is sensitive to extreme temperatures at seedling stage, which may cause yield loss. This study was conducted to explore the biosynthetic regulative mechanism of AsA and folates in sweet corn seedlings under temperature stress. RESULTS: The AsA and folate composition and relative gene expression in sweet corn seedlings grown under different temperature stresses (10, 25, and 40 °C) were evaluated. The imposition of temperature stress altered the AsA content mainly by modulating the expression of Zm DHAR, whose encoded enzyme dehydroascorbic reductase (DHAR) is essential in the AsA recycle pathway. Low temperature stress raised the expressions of relative genes, leading to folate accumulation. High temperature stress modulated the folate content by influencing the expression of the correspondence gene for aminodeoxychorismate synthase, Zm ADCS, as well as downstream genes that connected with DNA methylation. CONCLUSION: These results provided a theoretical basis, at a genetic level, for understanding the stress responses mechanism in sweet corn seedlings, offering guidance for sweet corn cultivation. © 2019 Society of Chemical Industry